2019
DOI: 10.1097/tp.0000000000002416
|View full text |Cite
|
Sign up to set email alerts
|

Islet Allotransplantation in the Bone Marrow of Patients With Type 1 Diabetes: A Pilot Randomized Trial

Abstract: BM is not a suitable alternative site for pancreatic islet allotransplantation in patients with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Furthermore, the bone marrow microenvironment post-transplantation of islets may contribute to the expansion of autoreactive T cells, such elevated concentrations of IL-7, or the low oxygen tension in the bone marrow despite very high vascular density. Finally, the authors concluded that the success seen in the pre-clinical and NHP models of T1D is difficult to replicate in humans without creating models of autoimmune-mediated rejection of pancreatic beta islets ( 75 ). Bone marrow as a transplantation site may not be ideal for pancreatic islet without first preconditioning the local bone marrow microenvironment for immune-modulation or cytoprotection with localized bone marrow irradiation ( 76 )…”
Section: Transplantation Sitesmentioning
confidence: 99%
“…Furthermore, the bone marrow microenvironment post-transplantation of islets may contribute to the expansion of autoreactive T cells, such elevated concentrations of IL-7, or the low oxygen tension in the bone marrow despite very high vascular density. Finally, the authors concluded that the success seen in the pre-clinical and NHP models of T1D is difficult to replicate in humans without creating models of autoimmune-mediated rejection of pancreatic beta islets ( 75 ). Bone marrow as a transplantation site may not be ideal for pancreatic islet without first preconditioning the local bone marrow microenvironment for immune-modulation or cytoprotection with localized bone marrow irradiation ( 76 )…”
Section: Transplantation Sitesmentioning
confidence: 99%
“…Only a few alternative transplantation sites have been tested in clinical trials so far: the bone marrow (15), the muscle of the forearm (16,17), and the omentum (18)(19)(20). Despite positive outcomes for autologous islet transplantation, clinical trials have shown that the bone marrow site is not a suitable alternative site for pancreatic islet allotransplantation in T1D patients, due to recurrence of autoimmunity (21). Survival of alloislets in the intramuscular site has also been shown to be limited so far (17).…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?mentioning
confidence: 99%
“…Thus, one area of ongoing research is the utility of alternate sites for islet allotransplant. Alloislet transplantation into bone marrow was unsuccessful in one small trial, while a biological scaffold created by layering islets with thrombin in an omental pouch has shown some early success, but was not superior to transplanting islets into the liver site [25]. One appeal of creating a biological omental scaffold is that this type of implantation site could allow future transplant-site engineering, including adding trophic factors or local immunoprotection strategies to the scaffold environment [26].…”
Section: Human Islet Transplantationmentioning
confidence: 99%